2016
DOI: 10.1111/cmi.12666
|View full text |Cite
|
Sign up to set email alerts
|

Mpn491, a secreted nuclease ofMycoplasma pneumoniae, plays a critical role in evading killing by neutrophil extracellular traps

Abstract: Neutrophils play an important role in antimicrobial defense as the first line of innate immune system. Recently, the release of neutrophil extracellular traps (NETs) has been identified as a killing mechanism of neutrophils against invading microbes. Mycoplasma pneumoniae, a causative agent of respiratory infection, has been shown to be resistant to in vitro killing by neutrophils, suggesting that the bacterium might circumvent bactericidal activity of NETs. In this study, we investigated whether M. pneumoniae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 52 publications
0
45
0
Order By: Relevance
“…Airway hypersecretion, epithelial desquamation, and remodeling cause AO, which compromises further clearance in vitro [7] , which was consistent with our present study. Other studies have shown that MP is resistant to killing by neutrophils, suggesting that the bacterium might circumvent bactericidal activity of neutrophil extracellular traps [14] . B cells and MP-specific antibodies are also crucial for its clearance in the lungs of mice [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Airway hypersecretion, epithelial desquamation, and remodeling cause AO, which compromises further clearance in vitro [7] , which was consistent with our present study. Other studies have shown that MP is resistant to killing by neutrophils, suggesting that the bacterium might circumvent bactericidal activity of neutrophil extracellular traps [14] . B cells and MP-specific antibodies are also crucial for its clearance in the lungs of mice [15] .…”
Section: Discussionmentioning
confidence: 99%
“…S. pneumoniae, Staphylococcus aureus, M. pneumoniae and other upper respiratory tract pathogens have exhibited nuclease activity in which there is a higher rate of bacterial survival when the nucleases are employed (7,58). The complete extent of nuclease utilization by these pathogens is not greatly understood, however, the nuclease proves to be beneficial in deconstructing an immune defense mounted against the pathogens, aiding in their survival.…”
Section: Bacterial Resistance Mechanismsmentioning
confidence: 99%
“…Mycoplasma pneumoniae, a human pathogen, is able to evade NET-mediated killing by degrading extracellular traps via a secreted nuclease (7). The conditional release of NETs and their direct role in the innate immune system is still to be fully understood, but several studies indicate that NETs are seen in infections with pathogens that are either too large to be phagocytized (i.e., fungal hyphae, bacterial aggregates) or evade phagocytosis entirely (61).…”
Section: Mycoplasma Interaction With Netsmentioning
confidence: 99%
See 2 more Smart Citations